The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1093/bja/aeh228
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration and the laryngeal mask airway: three cases and a review of the literature †

Abstract: The primary limitation of the laryngeal mask airway (LMA) is that it does not reliably protect the lungs from regurgitated stomach content. We describe three cases of aspiration associated with the LMA, including the first brain injury, the first death, and the first associated with the intubating LMA, and review the 20 specific case reports of aspiration associated with the LMA that we were able to find described in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 23 publications
(20 reference statements)
0
58
0
3
Order By: Relevance
“…The peripharyngeal gas leakage and gastric insufflation were stopped by simple manipulation; therefore, further gastric insufflations did not occur. However, pulmonary aspiration of gastric contents remains a major concern when using SLA devices, 15,16 and this occurrence is considered more prevalent during laparoscopic surgery in gynecology patients. 17 We should be all the more attentive to perilaryngeal leaks, consequent gastric insufflations, and pulmonary aspiration when using an SLA fitted with a cuff.…”
Section: Discussionmentioning
confidence: 99%
“…The peripharyngeal gas leakage and gastric insufflation were stopped by simple manipulation; therefore, further gastric insufflations did not occur. However, pulmonary aspiration of gastric contents remains a major concern when using SLA devices, 15,16 and this occurrence is considered more prevalent during laparoscopic surgery in gynecology patients. 17 We should be all the more attentive to perilaryngeal leaks, consequent gastric insufflations, and pulmonary aspiration when using an SLA fitted with a cuff.…”
Section: Discussionmentioning
confidence: 99%
“…We have no data on whether aspiration risk is higher when using an FT-LMA to place an ETT than when an ETT is placed using other methods. Keller et al 87 reported a case of aspiration associated with the elective use of the FT-LMA in a patient with an asymptomatic hiatal hernia. In their case, no exceptional events took place prior to the regurgitation episode, i.e., difficult insertion or an inability to ventilate with low peak pressure.…”
Section: Complications and Limitationsmentioning
confidence: 99%
“…In spite of the low incidence of aspiration associated with the laryngeal mask [24], it should be used with caution in patients at increased risk of aspiration [25]. The practice of exchanging the laryngeal mask for a tracheal tube is a well recognised method of avoiding problems at extubation [23].…”
Section: Managing Tracheal Extubationmentioning
confidence: 99%